FEA_LiNbO3: Finite element analysis of novel LiNbO3 material based fiber for optical communication properties of nonlinear applications - Ruhul Amin; Rana M. Taha; Baraa Riyadh Altahan; Noor Mohammadd; Kawsar Ahmed; Francis M. Bui; Fahad Ahmed Al-Zahrani; Shobhit K. Patel (Alexandria Engineering Journal, 2022)
This study introduces a distinctive LiNbO3-based five-ring heptagonal-shaped photonic crystal fiber (PCF) geometry that demonstrates exceptionally high birefringence (Br) and nonlinear coefficient (NLC). Fundamental simulation studies are conducted through the COMSOL software utilizing the finite element method (FEM) with a perfectly matched layer (PML) boundary condition in order to comprehensively explore a variety of relevant optical characteristics, including birefringence, effective area, nonlinearity, core power fraction, dispersion, numerical aperture, confinement loss and so on. The simulation outcomes reveal an ultra-high Br and NLC of 0.081 and 5843.32 W-1Km-1 sequentially, at the operative wavelength of 1.55μm. The designed PCF with ultra-high Br and NLC features can be fabricated suitably, which is an advantageous aspect for potential prospective utilization in polarization-maintaining, nonlinear optics, supercontinuum generation, etc.